Analysis of Students' Literacy Skills in Identifying Intrinsic Elements of Moral Values in Folktales at Elementary Schools - Sari, Ersi Mutia; Sapri, Sapri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The research was conducted at Elementary School 112321 Kampung Pajak. The aim of this study was to assess students' literacy skills in analyzing the intrinsic elements and moral values in folktales "Batu Menangis, Danau Situ Bagendit, Malin Kundang" at the elementary school level. The research utilized a qualitative descriptive approach, and the research population included classes V A, B, and C, with class V-B chosen as the research sample. Data were collected through observation, interviews, documentation, and written tests. Data analysis techniques involved data reduction, data presentation, verification, and data validity through triangulation. Based on the conducted research, the findings revealed that the literacy skills of students in determining intrinsic elements and moral values in the folktales in class V-B were categorized as "Good" and aligned with the Minimum Mastery Criteria (KKM) for the Indonesian language subject applied at Elementary School 112321 Kampung Pajak, which is set at 75. The evidence came from the analysis of written tests in the form of essay questions. Among the total of 18 students, 2 students demonstrated "Very Good" proficiency, 7 students showed "Good" proficiency, 6 students were categorized as "Satisfactory," and 3 students were categorized as "Insufficient." Nevertheless, students still need extensive practice in speaking, listening, reading, and writing, and one of the ways to achieve this is through regular visits to the school library.